The evaluation of the professional development of English faculties from their own vision of excellence - Daniel González González; Slava López Rodríguez (Universidad de Granada, 2013)
The general objective of this paper is to offer a system of teaching excellence indicators for the faculties of English as a foreign language in Cuba to guide their evaluation, training and professional development, considering the different stages of their academic career. Quality studies have been highly demanded in the educational field in the last decade. Accreditation processes and systems have been created and implemented to evaluate the excellence of teaching at universities worldwide. Cuban universities are not apart from that reality, facultiesʼ professional development is an important element to be considered however no indicators have been defined to evaluate and guide their performance. The model adopted in this research is the descriptive one. It was carried out in three stages so as to describe the vision of excellence professors of English in Cuba have of their professional development and the indicators they consider valid to evaluate their own work. For the analysis of the qualitative information we have carried out a deep content analysis and to analyze the quantitative information we used SSPS.